My Friend, the stranger: Somali spaza shop operators in the villages around Cofimvaba, Eastern Cape, South Africa - Maselwa, Avuyile (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
This thesis presents a study of the relationships between Somali spaza operators and the villagers living in the villages around Cofimvaba. The Somali spaza operators are operating spazas in the villages around Cofimvaba in the Intsika Yethu District Municipality (IYDM) located in the Chris Hani District Municipality (CHDM). Spaza shops are general dealers selling daily consumption items, which usually operate in the informal sector, primarily in poorer black neighbourhoods, both urban and rural. Resentment of the very visible, post-apartheid, expansion of immigrant entrepreneurship - in the informal sector, notably in spazas- has been central to South African anti-immigrant sentiment, popularly dubbed "xenophobia," which casts foreigners, mainly black or Asian, as stealing South African resources. Foreign spaza operators, many of them Somalis, have been subject to ongoing violence and looting for well over a decade, notably in the Eastern Cape and Western Cape provinces. Yet in the deeply impoverished villages around Cofimvaba, in the former Transkei black homeland in the Eastern Cape, where Somalis play a central and growing role in spazas, such attacks are unknown. The aim of this thesis is to understand why. Careful qualitative research in several villages has indicated key reasons. These include the relative absence of South African, locally- owned spazas, and so, the lack of a local group driving xenophobic resentment; the convenience offered by Somali-owned spazas in these isolated villages, the affordability of the products offered, and the availability of systems of credit for villagers; the investment of the Somali entrepreneurs into the villages through acts like charity; and their social interaction with villagers. The Somalis have redefined the local spaza sector, to the benefit of the villagers, and there is a degree of "xenophilia" as a result. The research also found that the growing number of Somali spaza operators in the villages was a direct result of the xenophobia experienced by this group in the urban townships. The villages around Cofimvaba benefit the Somali operator, not in a financial sense as these are not where the most profits have been made, but as sites where the traders feel safest. But although the villages are a sort of refuge, they are isolated and isolating. The Somalis resident in these areas struggle to maintain the strong ethnic group consciousness based on a strong vision of the Somali homeland, and a sense of being sojourners, hoping to relocate elsewhere.
Keywords: Immigrant business enterprises -- South Africa -- Eastern Cape; Somalis -- South Africa -- Eastern Cape; Somalis -- South Africa -- Eastern Cape -- Public opinion; Somalis -- South Africa -- Eastern Cape -- Case studies